The specifics of social work with victims of terrorism - Shimanovskaya, Yanina V. (2021)
The international situation in the modern world is characterized by instability, precariousness, and a high risk to the lives of people who may experience the negative consequences of emergencies arising from a variety of factors. Acts of terrorism belong to the phenomena of social emergencies of a criminal nature and currently represent one of the most widespread problems faced by 67% of modern developed and developing countries. Numerous terrorist acts compel heads of countries from around the world to come together and develop the most effective strategies to counter terrorism in their countries and the international community.